(untitled) (Світ фінансів, 2017)
Микитюк І. С. Основні вимоги до побудови єдиної системи державного фінансового контролю. Розглянуто концептуальні підходи щодо визначення вимог побудови Єдиної системи державногофінансового контролю та визначено власну позицію з цього питання. Mykytiuk I. Main requirements for the formation of the unified system of state financial control. Methodological approaches as to the defining requirements for the formation of the unified system of state financial control are considered and the position of the author on this problem is described.